Clinical utility of PCR for common viruses in acute respiratory illness - Rhedin, Samuel; Lindstrand, Ann; Rotzén-Östlund, Maria; Tolfvenstam, Thomas; Ohrmalm, Lars; Rinder, Malin Ryd; Zweygberg-Wirgart, Benita; Ortqvist, Ake; Henriques-Normark, Birgitta; Broliden, Kristina; Naucler, Pontus (Pediatrics (Evanston), 2014)
Acute respiratory illness (ARI) accounts for a large proportion of all visits to pediatric health facilities. Quantitative real-time polymerase chain reaction (qPCR) analyses allow sensitive detection of viral nucleic acids, but it is not clear to what extent specific viruses contribute to disease because many viruses have been detected in asymptomatic children. Better understanding of how to interpret viral findings is important to reduce unnecessary use of antibiotics. To compare viral qPCR findings from children with ARI versus asymptomatic control subjects. Nasopharyngeal aspirates were collected from children aged ≤5 years with ARI and from individually matched, asymptomatic, population-based control subjects during a noninfluenza season. Samples were analyzed by using qPCR for 16 viruses. Respiratory viruses were detected in 72.3% of the case patients (n = 151) and 35.4% of the control subjects (n = 74) (P = .001). Rhinovirus was the most common finding in both case patients and control subjects (47.9% and 21.5%, respectively), with a population-attributable proportion of 0.39 (95% confidence interval: 0.01 to 0.62). Metapneumovirus, parainfluenza viruses, and respiratory syncytial virus were highly overrepresented in case patients. Bocavirus was associated with ARI even after adjustment for coinfections with other viruses and was associated with severe disease. Enterovirus and coronavirus were equally common in case patients and control subjects. qPCR detection of respiratory syncytial virus, metapneumovirus, or parainfluenza viruses in children with ARI is likely to be causative of disease; detection of several other respiratory viruses must be interpreted with caution due to high detection rates in asymptomatic children.